COMPREHENSIVEANALYSISONTHEROLEOFINTERPROFESSIONAL COLLABORATION IN HEALTHCARE - Mahdi Hadi Mahdi Alyami, Nasser Mahdi Hamad Alyami Mohammed Mana Alsagri, MesferMohammedHadiAlsharyah, AlhassanHadiMohammedAlsulaiman, AbdullahNasserSaeedAlsalemAlYami, MunahiaMohammedMubarakAlyami (Chelonian Research Foundation, 2023)
Interprofessional collaboration (IPC) in healthcare has become a vital methodology for making strides in understanding care results and understanding complex well-being issues. This article gives a comprehensive survey of the part of IPC in healthcare, investigating its significance, benefits,challenges,andsuccessfulexecutionmethodologies.Bylookingintopertinent literature review, strategies, and proof, this review highlights the critical part of IPC in upgrading quiet security, moving forward with the quality-of-care control, progressing communication abilities, andmovingforwardwithassetutilization.Moreover,suggestionsareadvertisedtohealthcare AllthearticlespublishedbyChelo NonCommercial4.0Internationa Conservation and BiologyarelicensedunderaCreativeCommonsAttribution-enseBasedonaworkathttps://www.acgpublishing.com/ 2603 |Page organizations and approach creators to maximize the viabilityof IPC in treatment and advance a culture of collaboration. Keywords:Interprofessionalcollaboration,healthcare,patientcareoutcomes, communication, teamwork, healthcare quality.